Hepatitis B prevalence in Brazilian waste pickers: a systematic review with meta-analysis - Souza-Silva, Gabriel; Mol, Marcos Paulo Gomes (Revista de Saúde Pública, 2021)
OBJECTIVE: To describe the hepatitis B prevalence in Brazilian waste pickers. METHODS: We performed a literature search in the SciELO, Biblioteca Virtual em Saúde (BVS), PubMed and Web of Science databases using the descriptors: “hepatitis B” AND (“informal recycling” OR “waste picker” OR “recyclable waste collectors” OR “solid waste segregator”) AND (“recyclable waste” OR “solid waste”) AND Brazil. Epidemiological studies on HBV in Brazilian waste pickers published prior to February 2020 were included and evaluated for quality and bias using a funnel plot. RESULTS: This meta-analysis consisted of five articles. Prevalence of HBV surface antigen seropositivity was 14% (95%CI: 6%–22%) in Brazilian waste pickers. CONCLUSION: HBV prevalence in Brazilian waste pickers remains high. There should be more campaigns showing the importance of vaccination and personal protective equipment use.